Association Between Race/Ethnicity and Survival of Melanoma Patients in the United States Over 3 Decades: A Secondary Analysis of SEER Data. Issue 17 (April 2016) - Ward-Peterson, Melissa; Acuña, Juan M.; Alkhalifah, Mohammed K.; Nasiri, Abdulrahman M.; Al-Akeel, Elharith S.; Alkhaldi, Talal M.; Dawari, Sakhr A.; Aldaham, Sami A.
Abstract : Abstract: Melanoma is a treatable and preventable skin cancer. It is responsible for 75% of deaths among all skin cancers. Previous studies have found that race/ethnicity may play a role in survival among melanoma patients. However, there are no studies that cover 30 years and take race into account for the U.S. population. This study is a secondary analysis of the National Cancer Institute's Surveillance, Epidemiology, and End Result (SEER) Program. Adults with primary cutaneous melanoma from 1982 to 2011 were included; the final sample size was 185, 219. The outcome was survival; both cause-specific and all-cause mortality were examined. The main exposure was race/ethnicity. Kaplan–Meier survival analysis was used to estimate overall survival. Cox proportional hazards regression was used to estimate unadjusted and adjusted hazard ratios (HRs). A P -value less than 0.05 was considered statistically significant. More than 50% of patients in all races/ethnicities were diagnosed at the in situ or localized stage. Non-Hispanic White patients were more frequently diagnosed at the in situ stage. Overall, more men were diagnosed than women. The majority of cases among all races were men. Non-Hispanic Black females represented the smallest percentage of melanoma cases among all races. The smallest number of diagnoses across all races/ethnicities was made from 1982 to 1991. Median follow-up was 81 months and no collinearity was observed in the adjusted models. When examining cause-specific mortality and controlling for site and stage at diagnosis, gender, age and decade of diagnosis, the HR for non-Hispanic Black patients was lower than that for non-Hispanic White patients (HR 0.7; 95% confidence interval (CI): 0.6–0.8). However, when examining all-cause mortality, this difference disappeared (HR 1.1; 95% CI: 1.0–1.2). Stage at diagnosis impacted HR; patients diagnosed with distant metastases had significantly worse survival. When taking cause-specific mortality into consideration and after controlling for stage and site at diagnosis, gender, and age and decade of diagnosis, non-Hispanic Black patients had a lower HR compared to non-Hispanic White patients. However, this difference disappeared when examining all-cause mortality. Further research is needed to explore this finding and to determine what factors may be associated with late-stage melanoma diagnosis.